Immunization Status of Children and Its Association with Maternal Education - Muhammad Ahmed , Maria Sharif , Ali Sufyan , Mudassir Sharif Bhatti , Rai Muhammad Asghar, Muhammad Ahmed , Maria Sharif , Ali Sufyan , Mudassir Sharif Bhatti , Rai Muhammad Asghar (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: The Expanded Programme on Immunization was implemented in Pakistan in 1978 in collaboration with WHO and UNICEF. Pakistan being a developing country is still struggling to meet its goals. Educational status and knowledge of the mother has a key role in the success of immunization programme. Objective: To assess the immunization status of children and the impact of maternal level of education on the immunization status of children between the ages of 15-36 months at RMU Allied Hospitals. Methods: A cross sectional study was conducted on 380 respondents visiting Outpatient Department of Paediatrics, RMU allied hospitals. Mothers of the children of age group 15-36 months were included in the study via non-probability consecutive sampling technique and were interviewed using a structured questionnaire. Statistical data was analyzed using SPSS version 23. Results: 303 (79.7%) of the children were fully immunized, 66 (17.9%) were partially immunized and 11 (2.9%) had not received any immunization. 115 (68.04%) children of illiterate mothers, 145 (87.7%) children of mothers with education up to matriculation and 43 (93.47%) children of mothers with higher education were fully vaccinated. Conclusion: Vaccination status of children presenting at RMU allied hospitals was quite satisfactory. Mothers who have attained a higher degree of education are more likely to completely vaccinate their child as compared to those with a lower level of education or those who are uneducated. Keywords: EPI, Immunization status, Vaccination, Maternal Education